The fictionalization of morality police in Saudi novel: a new historicist approach - Mohammed Albalawi (Humanities & Social Sciences Communications)
Abstract The morality police have always inspired different, often conflicting, feelings in Saudi society. While many have supported the morality police, others saw their old privileges as problematic. Representations of and attitudes toward the morality police have been reflected in Saudi fiction in a broad multitude of works. However, research on the contextualization of the morality police in Saudi literature is often overlooked by literary critics. This study adopts a New Historicist approach and consults select literary works to examine fictional depictions of the morality police. The focus will be limited to three Saudi novels spanning from 2005 to 2009: Abdo Khal’s Immorality (2005), Samar Almogren’s Women of Vice (2008), and Yousef Al-Mohaimeed’s Where Pigeons Don’t Fly (2009/2014). The study attempts to show how Saudi literature offers representations of the morality police that can allow for a more profound insight into their role and its many implications.